2011
DOI: 10.5137/1019-5149.jtn.4171-11.0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in liliequist membrane in hydrocephalic process and its implications for endoscopic third ventriculostomy procedure

Abstract: AIm: Fenestration of Liliequist membrane (LM) during endoscopic third ventriculostomy (ETV) is extremely important for the success of the procedure. It is noteworthy that LM usually shows a tough and dense stucture in long-standing hydrocephalus cases different from its usual arachnoidal membrane-like structure observed in new-onset hydrocephalus cases. The structural variation of LM in different hydrocephalic states was investigated histologically in this study. mAterIAl and methOds: Specimens of LM obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Liliequist membrane (LM) forms a complete division in the basal subarachnoid space [21]. Thus; LM fenestration has crucial importance for success of ETV [23]. LM is thicker and more resistant in patients with long-standing hydrocephalus when compared with LM in patients who have newly developed hydrocephaly.…”
Section: Liliequist Membrane Patency and Its Morphologymentioning
confidence: 99%
“…Liliequist membrane (LM) forms a complete division in the basal subarachnoid space [21]. Thus; LM fenestration has crucial importance for success of ETV [23]. LM is thicker and more resistant in patients with long-standing hydrocephalus when compared with LM in patients who have newly developed hydrocephaly.…”
Section: Liliequist Membrane Patency and Its Morphologymentioning
confidence: 99%
“…Endoscopic: Endoscopic surgeries are being increasingly used in brain (16,17,40,49,64), spine (60) and skull base lesions (2, 3, 7, 10). Microsurgical technique and the combination of endoscopic visual control offers an effective minimally invasive approach (8).…”
Section: Microscopic Transcortical Transforaminal Resectionmentioning
confidence: 99%
“…Findings of Oi [31] also showed that the duration of hydrocephalus might cause various intraventricular anomalies [31]. Etus [32] also found associated histological changes in the structure of LM. The author showed that in recent-onset hydrocephalus, LM assumes its usual membrane-like, arachnoidal structure.…”
Section: Endoscopic Third Ventriculostomy (Etv)mentioning
confidence: 88%
“…Etus [32] also advised against using lasers and hot coagulating probes during the fenestration, regardless of the maneuver used, due to possible accidental injury to the basilar artery or the oculomotor nerve.…”
Section: Endoscopic Third Ventriculostomy (Etv)mentioning
confidence: 99%